Fibromyalgia syndrome and small fiber, early or mild sensory polyneuropathy. Issue 5 (26th April 2018) - Lawson, Victoria H.; Grewal, Jessie; Hackshaw, Kevin V.; Mongiovi, Phillip C.; Stino, Amro M.
ABSTRACT: Introduction : Pain mechanisms in fibromyalgia syndrome (FMS) are not clearly understood. Growing evidence appears to suggest a role for small fiber polyneuropathy (SFPN) in some FMS patients, as measured by epidermal nerve fiber density (ENFD). We aimed to better characterize and distinguish the subset of patients with both fibromyalgia and small fiber, early or mild sensory polyneuropathy (FM‐SFSPN). Methods : 155 FMS patients with neuropathic symptoms completed a Short Form McGill Questionnaire and visual analog scale in addition to having skin biopsies, nerve conduction studies (NCS), and serologic testing. Results : Sural and medial plantar (MP) response amplitudes correlated with ENFD, with markers of metabolic syndrome being more prevalent in this subset of patients. Pain intensity and quality did not distinguish patients. Discussion : The FM‐SFSPN subset of patients may be identified through sural and MP sensory NCS and/or skin biopsy but cannot be identified by pain features and intensity. Muscle Nerve 58 : 625–630, 2018